SOME ASOCIATED FACTOR RELATED TO MEDICAL SOLID MANAGEMENT IN KRONG BONG GENERAL HOSPITAL, DAKLAK PROVINCE, 2019 (Vietnam Journal of Community Medicine, 2022)
Objective: To describe some associated factors related to medical solid management in Krong Bong General Hospital, in Daklak, 2019Method: A qualitative cross-sectional study (in-depth interviews, group discussions) was conducted from March to August 2019 in Krong Bong General Hospital, in DaklakResults: Some factors affecting the management of solid waste at Krong Bong General Hospital could be classified into 6 groups, including: Positive influences: 1) Policy factors, 2) Management leadership factors, 3) Factors belonging to medical staff. Obstacles: 4) Facilities, equipment, 5) Financial factors, and6) Other factors
Keywords: Medical solid waste, associated factor, management, Daklak.